Treatment of whey wastewater by electro-Fenton and photocatalytic hybrid process - Mogol, H. M.; Akgun, M. (SPRINGER, 2025)
This study investigates the sequential treatment of diluted whey wastewater using electro-Fenton and UV/photocatalytic methods with a hybrid process approach. Anatase TiO2, Fe-doped, and N-doped TiO2 catalysts were used in the experiments. To gain a comprehensive understanding of the prepared catalysts, multiple analytical techniques were employed, including scanning electron microscopy (SEM), Brunauer-Emmett-Teller (BET) surface area analysis, X-ray diffraction (XRD), and Raman spectroscopy. Particle size and surface area of Fe-doped and N-doped TiO2 catalysts were measured as 44.70 nm and 31.96 m2/g for Fe-doped, and 34.21 nm and 41.76 m2/g for N-doped TiO2, respectively. The crystal size and crystallinity percentage of both doped catalysts were found to be around 12-14 nm and 80%, respectively. In the photocatalytic treatment experiments, the effects of parameters such as pH, catalyst amount, and H2O2 concentration were investigated. According to the results, the total organic carbon (TOC) removal efficiency obtained with Anatase TiO2 (46.57%) was found to be slightly higher compared to the TOC removal efficiencies of Fe and N-doped catalysts (36.32% and 37.58%, respectively). When examining the sequential treatment TOC removal efficiency, it was observed that using 2 g/L Anatase TiO2 at pH 2, a mineralization efficiency of 69.48% could be achieved within 3 h.
Keywords: Whey wastewater; Treatment; Electro-Fenton; Photocatalytic; Titanium dioxide; CHEESE-WHEY; DOPED TIO2; ANAEROBIC TREATMENT; DEGRADATION; OXIDATION; REACTOR; NANOPARTICLES; DEMINERALIZATION; DISINFECTION; WASTEWATERS; Environmental Sciences & Ecology